ADDITIVE FOR CELLULOSE ACETATE MEMBRANE FROM COCONUT SAP IN DESALINATION APPLICATION - Widyaningsih, Senny; Chasani, Mochamad; Zusfahair, Zusfahair; Anam, Muhamad Sofie Khaerul; Anisya, Alny Nur (Malaysian Journal of Science, 2020)
The cellulose acetate membrane based on coconut sap was successfully synthesized by phase inversion method. Membrane application on desalination has been done to know membrane performance. The additive can affect the membrane performance. This research was conducted to find out the effect of the additive. The additives are polyethylene glycol (PEG) and formamide. Membrane characterization studied including flux, rejection, tensile strength, and pore size. The result showed that cellulose acetate membrane with PEG has 7.08 L/(m2.h) of flux and 32.23% of rejection. While membrane with formamide has 7.08 L/(m2.h) of flux and 46% of rejection. The additive can increase the membrane performance. Formamide additive gives a better membrane characteristic than PEG.